PENGARUH LINGKUNGAN KERJA DAN PENGEMBANGAN KARIR TERHADAP RETENSI KARYAWAN PADA HOTEL SANTIKA NUSA DUA BALI - Pratiwi, Luh Putu Yunia Anggy; Sriathi, Anak Agung Ayu (E-Jurnal Manajemen; Vol 6 No 3 (2017), 2017)
The purpose of this study was to elucidate the employee retention, non-physical work environment and career development. Retention of employees is the company's efforts in maintaining well-performing employees to remain in the company for a certain period. The research was carried out at the Santika Hotel Nusa Dua Bali. The study population was all employees amounted to 84 people, using saturated sample. Data were collected by means of observation, interviews and questionnaires in the form of a questionnaire. Analyzer used multiple linear regression analysis techniques, and F. Test results showed that non-physical work environment and career development is positive and significant effect on the retention of employees, the higher the non-physical work environment and career development, the higher the level of employee retention.
Keywords: non physical work environment, career development, employee retention